Exploring the Negotiation Strategy of Nepal at World Trade Organization (Prashasan: The Nepalese Journal of Public Administration, 2023)
The Political Economy of neo-liberalization is supposed to benefit countries that adopted liberal trade policies.  As the key driver, the World Trade Organization (WTO) establishes the minimum requirements for numerous agreements on goods, services, intellectual property, trade facilitation, and development elements of international trade. These agreements provide special and differential provisions for the Least Developed Countries (LDCs) and developing countries to be benefited from trade liberalization. This study analyzes the effectiveness of Nepal's economic diplomacy; particularly its negotiation strategy in various WTO agendas. This study finds that WTO agreements help emerging developing nations in improving their trade performance and attract foreign direct investment where Nepal and many other LDCs are performing weaker roles in trade negotiation resulting in a lower level of trade and investment. Therefore, this study offers some recommendations for fostering economic trade negotiation aspects of economic diplomacy.